REPRESENTING THE HOLY GRAIL ON RELIQUARY SARCOPHAGI IN SYRIA - Dana KHOULI (Journal of Ancient History and Archaeology)
This scholarly article examines the depiction of the Holy Chalice within a significant category of Christian reliquaries, with a specific focus on examples from Syria. The research delves into the analysis of numerous sarcophagi reliquaries distinguished by their utilization of the libation system and explores the various artistic representations of the Chalice within this context.